Improving Mathematics Learning Outcomes Through Contextual Teaching Learning (CTL) Models with Auxiliary Objects of the Surrounding Environment at Madigondo Samigaluh Public Elementary School, Kulon Progo Regency, 2021/2022 Academic Year - Fembri Susilawati (IJCER (International Journal of Chemistry Education Research), 2023)
This research was conducted to improve mathematics learning outcomes in the 2019 Coronavirus Disease (Covid-19) pandemic era through face-to-face meetings, increase student motivation in learning and improve teachers' abilities in carrying out teaching and learning activities. This type of research is Classroom Action Research (CAR). The subjects of this study were all fifth-grade students at SD Negeri Madigondo Kapanewon Samigaluh for the 2021/2022 academic year, with a total of 14 students consisting of 9 boys and 5 girls. The object of research is solving problems related to learning mathematics by using the CTL learning model to increase student motivation and achievement as well as teaching abilities in teaching and learning activities. The data collection technique in this study used the evaluation of student test assessments and observation sheets. The results showed that there was an increase in students' mathematics learning outcomes through the CTL learning model, namely in cycle I for 1st meeting of 55.56% in the "very low" category, and in 2nd meeting, the percentage of learning completeness was obtained by 66.67% in the "low" category, while in cycle II for 1st meeting percentage of 77.78% category "Enough" and at 2nd meeting obtained a percentage of 100%. The results showed that there was an increase in the learning motivation of fifth-grade students at SD Negeri Madigondo Kapanewon Samigaluh, namely in cycle I for the 1st meeting obtained a percentage of 49.39%, and the 2nd meeting obtained a percentage of 70.31%. While in cycle II for 1st meeting obtained a percentage of 84.60%, and the second meeting obtained a percentage of 92.70%. The results showed an increase in the current teacher's ability (KBM), that is, in cycle I a presentation of 89.68% was obtained with a conversion of 4 "Very Satisfactory" values, while in cycle II a percentage of 95.91% was obtained with a conversion of 4 "Very Satisfactory" values.